Dinamika Psikologis pada Wanita Menggugat Cerai Suami - Dwi Rahmalia; Nurvica Sary (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2018)
This research aim to know how is the psychoogical dynamic of the wife who sued for divorce from husband. This research is using the qualitative method specifically in phenomenological approach. There are 3 informants of this research, which are 3 marriage women with more than 3 years age of marriage. The data taken by interview and observation. The Result of this research the psychological dynamic shows : guilt to the child, trauma to marriage, anxiety or worry in choosing the right partner and disappointment of the concept of marriage that is not in accordance with reality.